The Development of Teaching Material Based on Science, Technology, Engineering, and Mathematics (STEM) - Abdul Rahman; Muhammad Arsyad; Kaharuddin Arafah (Universitas Muhammadiyah Makassar, 2021)
This research is a development research that aims to describe a valid profile of STEM-based teaching material development, analyze students' responses to the development of teaching materials and analyze the effectiveness of STEM-based teaching materials to examine creative thinking skills. This research was conducted at SMAN 9 Makassar in class XI MIA 6 consisting of 32 students as respondents. STEM-based physics learning was carried out 5 times on static and dynamic fluid material. Learning activities contain four elements, namely science, technology, engineering and mathematics, and the STEM results made are making hydraulic bridges and simple mosquito sprays from used materials. The development model used was ADDIE which consists of analysis, design, development, implementation and evaluation. The ADDIE model is a development procedure carried out by producing a STEM-based physics learning product. The intended product is to produce a STEM-based physics teaching material, step-by-step. These steps are included in the teaching material that must be validated and ready to be used by the teachers in carrying out learning so that students can think creatively. The results showed the practicality of physics teaching material based on practical STEM. It was seen from the results of the responses of students and the responses of teachers who were in the very good category. Learning using STEM-based teaching materials is effective and can make students think creatively. This is shown in the fluency thinking indicator with a percentage of 74.58%, the flexible thinking indicator 71.25%, the original thinking indicator 81.56%, and the elaborative thinking indicator 82.03%, with an average percentage of 77.36% which is in the creative category.